Female patients with follicular lymphoma have a better prognosis if primary remission lasts over 24 months. Issue 7 (7th June 2021) - Rajamäki, Aino; Sunela, Kaisa; Prusila, Roosa E. I.; Kuusisto, Milla E. L.; Mercadal, Santiago; Selander, Tuomas; Kuitunen, Hanne; Pollari, Marjukka; Jantunen, Esa; Nystrand, Ilja; Sancho, Juan-Manuel; Sorigue, Marc; et al.
Abstract: Findings regarding the role of sex in follicular lymphoma (FL) are contradictory and the prognostic value of sex among patients with early progression of disease (POD) remains unclear. We collected real-life data from nine hospitals in Finland and Spain including 1020 FL patients to study the influence of sex on disease outcome. The median follow-up duration was 67 months (range 0–226 months). Female patients showed better progression-free survival (PFS) (hazard ratio [HR], 0.720; 95% confidence interval [CI], 0.588–0.881), disease-specific survival (DSS) (HR, 0.653; 95% CI, 0.448–0.951), and overall survival (OS) (HR, 0.653; 95% CI, 0.501–0.853) than male patients. However, there were no significant sex differences in prognosis in patients with early POD. This study strengthens the understanding that male sex is an adverse prognostic factor for FL. However, this difference does not apply to patients with early POD.